Perbandingan Hasil Belajar Online dan Offline pada Mata Kuliah Bahasa Inggris Mahasiswa Program Studi Kebidanan - Kusmayra Ambarwati (Departement of Mathematics Education, 2023)
Because of the Covid-19 outbreak, educational institutions must continue to provide instruction while adhering to health procedures. Distance online learning is one type of learning innovation practised. The implementation of this type of learning has both advantages and problems, particularly for students learning outside of their primary education major, as in this study, specifically students in the Midwifery study programme learning English. The purpose of this study is to determine the outcomes of online learning, such as student opinions and satisfaction, and to compare the results of learning outcomes between online and online learning in English courses. This research utilized a mixed method, with quantitative data supplemented by in-depth interviews with students enrolled in online programmes. This study included 20 students from the Midwifery study programme, with data gathered from secondary sources on students who had participated in offline learning before the pandemic (20 students) and primary sources received from students who participated in online learning. There was no significant difference in the average value of student learning outcomes between online and non-online, according to the findings. The majority of students are happy with the many types and methods of online learning. Further research on the clarity of learning outcomes is required, with larger samples and more detailed variables.